2015
DOI: 10.1093/nar/gkv995
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the enzymatic role of EF-G in ribosome recycling

Abstract: During translation, elongation factor G (EF-G) plays a catalytic role in tRNA translocation and a facilitative role in ribosome recycling. By stabilizing the rotated ribosome and interacting with ribosome recycling factor (RRF), EF-G was hypothesized to induce the domain rotations of RRF, which subsequently performs the function of splitting the major intersubunit bridges and thus separates the ribosome into subunits for recycling. Here, with systematic mutagenesis, FRET analysis and cryo-EM single particle ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
0
16
1
Order By: Relevance
“…However RRF could not split pre-formed 70S-EFG-GTP complex and addition of unfolded protein to this after 7 min resulted in ribosome dissociation at as fast a rate as it does to free 70S (Fig 5B [D] ). These results go in favor of the previous reports where structural studies revealed that RRF, EFG share some overlapping binding sites on the ribosome and it is the EFG that pushes RRF during their concerted action for ribosomal subunit dissociation [13, 14]. Thus RRF and unfolded protein access their respective binding sites on ribosome through different routes.…”
Section: Resultscontrasting
confidence: 61%
See 3 more Smart Citations
“…However RRF could not split pre-formed 70S-EFG-GTP complex and addition of unfolded protein to this after 7 min resulted in ribosome dissociation at as fast a rate as it does to free 70S (Fig 5B [D] ). These results go in favor of the previous reports where structural studies revealed that RRF, EFG share some overlapping binding sites on the ribosome and it is the EFG that pushes RRF during their concerted action for ribosomal subunit dissociation [13, 14]. Thus RRF and unfolded protein access their respective binding sites on ribosome through different routes.…”
Section: Resultscontrasting
confidence: 61%
“…In presence of EFG-GMPPNP, the unfolded protein failed to split the 70S-tRNA complex (Fig 4B), similarly as RRF is unable to dissociate 70S-tRNA with EFG-GMPPNP and IF3 (Fig 4A). Presumably an EFG-GTP mediated structural transition of 70S-tRNA complex leading to dissociation of tRNA [13, 14] is necessary for RRF or unfolded protein to split 70S.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6a ), thus forming an important ribosomal inter-subunit bridge (bridge 2a). H69 is also known to be involved in ribosome recycling 30 31 . Hyper-pseudouridylations occur on H39 (one U), helix H89 (four Us), H90 (one U) and H92 (two Us).…”
Section: Discussionmentioning
confidence: 99%